Modular OrCAD simulation approach in teaching power electronics - Darwish, Mohamed K.; Marouchos, Christos (My University, 2014)
In this paper the authors present a new technique which can be used in simulating multi power electronic circuits at the same time in a very accurate way without the worries of the circuit analysis being diverted during the simulation. In this technique each circuits is simulated alone and the output current/voltage waveform(s) of this circuit is presented as a 'wave-form' generator. Then the final multi circuit design will be a collection of these 'wave-form' generators. This technique can be used in teaching power electronics system design for undergraduate as well as postgraduate levels and can also be used in the industry. A UPS system is used as an example in demonstrating this technique but this approach could equally be applicable to other multi circuit design configurations.
Keywords: Education in Power Electronics; Modular Simulation; OrCAD; Power Electronics; PSPICE Simulation; Simulation in Power Electronics; UPS